CITRAAN DALAM KUMPULAN PUISI DAN KEMATIAN MAKIN AKRAB KARYA SUBAGIO SASTROWARDOYO - Jannah, Nor; Junal, Junal (Jurnal Sastra Aksara, 2019)
Imagery is one of the many poetic expression techniques used by poets to optimize the effect of affirming the sensory experience in the poet and arouse it to the reader or listener through written language. This study aims to describe the types of images in the collection of poetry Dan Kematian Makin Akrab the work of Subagio Sastrowardoyo. This study aims to describe (1) how the form of images in a collection of poetry and death is increasingly familiar to the work of Subagio Sastrowardoyo, (2) How is the meaning of imagery in a collection of poems Dan Kematian Makin Akrab the work of Subagio Sastrowardoyo. This research is in the collection of poetry Dan Kematian Makin Akrab the work of Subagio Sastrowardoyo using the concept of imagery. In addition to the concept of imagery, this study uses stylistic studies. This research is a qualitative descriptive study. This research data is in the form of quotations derived from the collection of poetry Dan Kematian Makin Akrab the work of Subagio Sastrowardoyo. The results of the research in a collection of poems Dan Kematian Makin Akrab the work of Subagio Sastrowardoyo found the existence of images in the form of form and meaning. In the form of images that contain 6 elements of imagery, there are images of vision, hearing, touch, smell, motion, and feeling. The meaning of this image uses clear images and creates an interesting atmosphere. Based on the analysis of the images in the collection of poetry Dan Kematian Makin Akrab the work of Subagio Sastrowardoyo, it can be concluded that the collection of poems uses images to express the poet's ideas and imagination. The imagery contained in a collection of poems is able to provide a clear picture and create a more lively and interesting atmosphere so that the reader can feel what the author meant in the poem.